2006
DOI: 10.1185/030079906x104795
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes in youth from the Western Pacific region: glycaemic control, diabetes care and complications

Abstract: The management of type 2 diabetes in youth from the Western Pacific Region varies widely. Hypertension and microalbuminuria were frequent, but not commonly treated. Further investigation into the natural history and risk factors for complications in youth with type 2 diabetes is required to assist in developing evidence based management guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 26 publications
3
94
0
Order By: Relevance
“…However, it is surprising that only two out of 55 patients screened had evidence of proteinuria; a recent US study reported a prevalence for an increased albumin/creatinine ratio in the first year after diagnosis of 16%,29 and Eppens et al 21 reported a prevalence of 28%, with a median disease duration of 1.3 years. However, the prevalence of hypertension in our cohort of 34% is similar to that reported from other studies, indicating significant levels of comorbidity 21 23…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it is surprising that only two out of 55 patients screened had evidence of proteinuria; a recent US study reported a prevalence for an increased albumin/creatinine ratio in the first year after diagnosis of 16%,29 and Eppens et al 21 reported a prevalence of 28%, with a median disease duration of 1.3 years. However, the prevalence of hypertension in our cohort of 34% is similar to that reported from other studies, indicating significant levels of comorbidity 21 23…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the median HbA1c at 1 year of 6.5% in our cohort is very similar to that reported in adults with newly diagnosed type 2 diabetes,22 indicating that, in some ways, the clinical course of paediatric type 2 diabetes is similar to that in adults. However, the range in our cohort was wide, and 40% of patients had a HbA1c concentration above 7.5%, an identical prevalence to that described in a study of 331 children with type 2 diabetes in the western Pacific region 23. Furthermore, 37% had a concentration >8.0%, which is associated with a substantially increased risk of complications 24 25…”
Section: Discussionsupporting
confidence: 65%
“…The pediatric literature is scant but available data suggests that glycemic control is also an important risk factor in youth with T2DM [30, 53]. However, the ideal target for HbA1c to minimize the risk of nephropathy in youth with T2DM has not yet been determined.…”
Section: Risk Factors For Progressionmentioning
confidence: 99%
“…In contrast to the T1DM and adult onset T2DM literature [65], which consistently demonstrates hypertension to be an important modifiable risk factor for the development and progression of diabetic nephropathy, the association between blood pressure control and microalbuminuria in adolescents with T2DM is inconsistent [32, 45, 53]. A small case-control study ( n = 23) revealed that daytime systolic blood pressure was ~8 mmHg higher among youth with T2DM, relative to normoalbuminuric controls [32].…”
Section: Risk Factors For Progressionmentioning
confidence: 99%
“…Pima Indian youth diagnosed with T2D were found to have prevalence rates of 18% HTN and 22% MA at T2D diagnosis, with estimated prevalence rates of MA of 60% and proteinuria of 17% before 30 years of age. [4043] A retrospective review of renovascular complication rates of individuals who were diagnosed with either T1D or T2D in youth was done in Manitoba, the province in Canada which has a predominantly minority/first nation population and the highest rate of T2D in Canada. Patients with a diagnosis of T1D or T2D were identified using International Classification of Diseases Ninth Revision (ICD9) codes, with subjects matched for age, sex, and postal code.…”
Section: Introductionmentioning
confidence: 99%